Atomic Imaging of Subsurface Interstitial Hydrogen and Insights into Surface Reactivity of Palladium Hydrides. Issue 46 (4th September 2020) - Lin, Bingqing; Wu, Xi; Xie, Lin; Kang, Yongqiang; Du, Hongda; Kang, Feiyu; Li, Jia; Gan, Lin
Abstract: Resolving interstitial hydrogen atoms at the surfaces and interfaces is crucial for understanding the mechanical and physicochemical properties of metal hydrides. Although palladium (Pd) hydrides hold important applications in hydrogen storage and electrocatalysis, the atomic position of interstitial hydrogen at Pd hydride near surfaces still remains undetermined. We report the first direct imaging of subsurface hydrogen atoms absorbed in Pd nanoparticles by using differentiated and integrated differential phase contrast within an aberration‐corrected scanning transmission electron microscope. In contrast to the well‐established octahedral interstitial sites for hydrogen in the bulk, subsurface hydrogen atoms are directly identified to occupy the tetrahedral interstices. DFT calculations show that the amount and the occupation type of subsurface hydrogen atoms play an indispensable role in fine‐tuning the electronic structure and associated chemical reactivity of the Pd surface. Abstract : Subsurface interstitial hydrogen atoms in Pd hydride nanoparticles are directly imaged by using differentiated and integrated differential phase contrast within an aberration‐corrected scanning transmission electron microscope. DFT calculations suggest that the amount and the occupation type of the subsurface hydrogen atoms is indispensable in fine‐tuning the electronic structure and chemical reactivity of the outmost Pd surface.